Novel haplotypes that underly higher higher head rice yield (HRY) in rice - CGIAR Research Program on Rice (2020)
Breeding material of high-yielding varieties exhibited moderate to poor HRY. Hence using diversity lines we identified the genetics controlling HRY and important donor lines identified, which has been deployed for pre-breeding efforts to minimize rice breakage during rice milling.